Inquéritos soroepidemiológicos em eqüinos da região Sul do Brasil para detecção de anticorpos anti-flavivírus de interesse em saúde pública - VIANNA, Ricardo da Silva Teixeira (2010)
The arboviruses are diseases that affect humans, horses and other animal species causing in the majority of cases an asymptomatic infection to neurological disorders. The Flaviviruses are important arbovirus found in Brazil. A descriptive study was conducted from serological surveys in 1775 horses for detection of anti-Flavivirus antibodies in the State of Paraná (Foz do Iguaçú, Maringá and Barracão), Santa Catarina (São Miguel do Oeste, Guaraciaba, Iraceminha, Dionisio Cerqueira, Guarujá do Sul and São José do Cedro) and Rio Grande do Sul (Uruguaiana, São Borja, Itaqui Alegrete and Porto Alegre) in the years of 2007 and 2008. By testing hemagglutination inhibition (HI) were detected HI antibodies of Saint Louis and Ilhéus and other Flaviviruses included in the tests, as well as cross-reactivity for Flaviviruses. By HI test, 14.3% (254/1775) of animals were positive for Flavivirus, monospecific reactions were observed in 42.9% (109/254) serum samples, being that 78.9% (86/109) for St. Louis, 17.4% (19/109) for Ilhéus and 3.7% (4 / 109) for Rocio and cross-reactions were detected in 57.1% (145/254). Among the positives, there was no difference between the sexes. The age group ≥ 10 years old was the most affected with 35.4% (73/206). The animals used for the practice of sport were positive in 34.3% (87/254). The state of Paraná showed 16.3% (107/657) of reacting animals, followed by Rio Grande do Sul with 15.1% (142/939) and Santa Catarina with 2.8% (5/179). This study brings new data regarding the immunity of horses against Flaviviruses in Brazil, and confirms the wide distribution of St. Louis and Ilhéus and the diversity of Flavivirus in the country, as well as the apparent absence of clinical disease in horses infected with the virus studied.